The Degree to which Individuals with Intellectual Disabilities Possess Self-Determination Skills from the Parents' Point of View - Mohammed Mohaidat; Maram Alkhatatbeh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to find out the degree to which adults with Intellectual disabilities have the skills of self-determination from the point of view of parents. The study also aims at finding out whether there are significant differences in the degree to which students with adult intellectual disabilities possess the skills of self-determination from their parent's point of view due to variables family economic level, severity of disability, age of individual, position, and private/public sector. To achieve the objectives of the study, a questionnaire on self-determination skills for parents was Developed. The study sample consisted of (131) parents of adults with Intellectual disabilities in the governorates of Irbid and Ajloun they were selected through the available way from the parents' community. The results revealed that the degree to which adults with Intellectual disabilities have the skills of self-determination and their axes from the parent's point of view has all been medium. The results showed statistically significant differences at the level of significance (α = 0.05) between the averages for the acquisition of self-determination skills by adults with Intellectual disabilities, from the perspective of the parents according to the degree of disability, and it was in favor of those of simple Intellectual disability, and the type of the public centers. The results also showed that there were no statistically significant differences at the level of (α = 0.05) between the averages for the adults' acquisition of self-determination skills from the parent's point of view according to age and the family's economic level.